Understanding hybridity in public organizations - Denis, Jean- Louis; Gestel, Nicolette Van; Ferlie, Ewan (2015)
This article explores and extends the concept of hybridity to understand current changes in public services organizations, notably as seen from an organizational studies perspective. The notion of hybridity has become more important, given that the public sector increasingly blurs with other sectors and more social actors. Previous reliance on the use of ideal-types in characterizing public services reforms has masked expanding heterogeneity. We here move beyond the (i) conventional focus on structural hybridity to consider (ii) institutional dynamics, (iii) social interactions, and (iv) new identities and roles in public services. Based on these four dimensions of hybridity, we review alternative theoretical frameworks. We suggest that bringing together work from the neighbouring disciplines of public administration and organization studies may improve our understanding of public services hybridity and outline a future research agenda. - Reproduced.
Keywords: Public administration